The Politics of Language: Why Sex is Not Work. Issue 2 (December 2017) - Gupta, Ruchira
This oral history is captured from a speech that the founder of Indian anti-sex trafficking organization, Apne Aap Women Worldwide, gave at an international conference, Last Girl First, in Delhi on 30 January 2017. The conference aimed at showcasing the intersecting inequalities of class, caste, gender, race, ethnicity, religion that make women and girls vulnerable to sex-trafficking. It highlighted through the voices of survivors, activists, labour leaders, politicians, doctors and academics, why prostitution is male sexual violence on women and how renaming it as 'sex-work' legitimises the exploitation. The author describes how she started Apne Aap, meaning self-action in Hindi with a few prostituted women, and learned from them and the other thousands of women who joined Apne Aap later, that their prostitution was an absence of choice, not a choice. She explains the consequences of language – how the term 'sex-worker' created policies that entrenched the exploitation of prostituted women, leaving no room for exit and excusing States from investing in the basic needs of The Last Girl and in the working rights of women.